Pengaruh Gaya Hidup Dan Kelompok Rujukan Terhadap Keputusan Tablet Pc di Kota Denpasar - Larasati, Ayu; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 2 No 12 (2013), 2013)
Tablet PC is one product that reflects that the industrial development of Communications, Hig-Tech, and Media (CMH) more innovative. This will be related to the emergence of tablet PC products in the market which introduced many brands in it. This phenomenon must be related to how consumers make purchase decisions that are faced with a variety of factors, one of which is related lifestyle activities, interests, and opinions that provide stimulus in the purchase decision and can not be separated from the influence of their environment is like a family reference group , friends, neighbors, celebrities, experts urge the inexperienced, the Common Man, and a spokesman for the executive. The purpose of this study was to determine the effect of lifestyle and a reference group of the tablet PC purchase decisions in Denpasar . Method in the determination of the sample using purposive sampling with 75 respondents. This study using multiple linear regression analysis. Research states that the independent variable lifestyle (X 1 ) and the reference group (X 2 ) simultaneously positive and significant impact on purchasing decisions tablet PC in Denpasar, partially also suggests lifestyle (X 1 ) and the reference group (X 2 ) influential positive and significant impact on purchasing decisions tablet PC in the city of Denpasar. Of the two independent variables which have a dominant influence is the reference group.   Keywords: L ifestyle , R eference G roup , P urchasing D ecisions
Keywords: Keywords: Lifestyle, Reference Group, Purchasing Decisions